2017
DOI: 10.1039/c7mb00001d
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Hexanedione induces autophagic death of VSC4.1 cells via a PI3K/Akt/mTOR pathway

Abstract: 2,5-Hexanedione (HD) is an important bioactive metabolite of n-hexane, which mediates the neurotoxicity of the parent compound. Increasing evidence suggests that over-activated autophagy can lead to autophagic neuronal death; however, whether the excessive autophagy is involved in HD-induced neurotoxicity remains unknown. To investigate the effect of HD on autophagy and to find its underlying mechanism, we respectively treated VSC4.1 cells with 5, 15 and 25 mM HD for 24 h. Our results show that HD induced exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Previous study reported that PI3K/Akt/mTOR pathway played an important role in regulating autophagy [ 22 ]. Therefore, we further explored whether miR-361-5p suppressed chemoresistance of GC cells through PI3K/Akt/mTOR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported that PI3K/Akt/mTOR pathway played an important role in regulating autophagy [ 22 ]. Therefore, we further explored whether miR-361-5p suppressed chemoresistance of GC cells through PI3K/Akt/mTOR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether high glucose affects autophagy, H9c2 cells were exposed with high glucose medium in the absence or presence of Exe (10 nM) or LIRA (100 nM) in the presence or absence of the autophagy inducer rapamycin (100 nM) or the autophagy inhibitor 3-methyladenine (3-MA, 10 mM) [ 23 ]. To assess the role of mTOR in Exe- and LIRA-induced response, if any, against high glucose-induced cardiomyocyte mechanical dysfunction, murine cardiomyocytes were exposed with high glucose medium in the absence or presence of Exe (10 nM) or LIRA (100 nM) for 4 hours with or without the mTOR activator [3-benzyl-5-((2-nitrophenoxy) methyl)-dihydrofuran-2(3H)-one (3BDO),120 μ M] [ 24 ] prior to assessment of mechanical function.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is mediated by various signal pathways, most of which were related to the PI3K/Akt/mTOR signaling pathway. 18 Here, we measured the expression of phosphorylated Akt (p-Akt) and mTOR in different groups by western blot. Our data showed that the low expression of p-Akt and mTOR induced by MI/R injury was up-regulated by vitexin treatment in a dosedependent manner (**P < 0.01, # P < 0.05, ## P < 0.01, Fig.…”
Section: Vitexin Mitigates Mi/r Injury Through Activation Of Pi3k/aktmentioning
confidence: 99%